Dampak Kerajinan Tikar Mendong Dalam Meningkatkan Perekonomian Masyarakat (Studi Kasus di Desa Lenek Kecamatan Lenek Kabupaten Lombok Timur) - Jusridayanti, Jusridayanti; Sholihah, Isfi (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2023)
This study aims to determine the impact of mendong mat crafts in improving the economy in Lenek village, namely regarding the level of income, poverty and purchasing power of the community. This study is a type of quantitative research with a causal associative method. The population is mendong mat craftsmen. A sample of 32 mendong mat craftsmen with a purposive sampling method. The analysis uses simple linear regression analysis. The results of this study indicate; 1) mendong mat crafts have a positive and significant impact on income. This can be seen from the t-count value which is greater than the t-table value (22.028> 2.051) with a significance level of 0.000 <0.05. 2) Mendong mat crafts have a positive and significant impact on poverty. This can be seen from the t-count value which is greater than the t-table value (2.412> 2.051) with a significance level of 0.022 <0.05. 3) Mendong mat crafts have a positive and significant impact on people's purchasing power. This can be seen from the t-value which is greater than the t-table value (2.380 > 2.051) with a significance level of 0.024 < 0.05. The higher the amount of production and sales, the income will increase, the number of poor people will decrease slightly because the level of absorption of labor energy increases and people's purchasing power will also increase because of the ability to meet needs more easily.